EVALUASI KINERJA PEGAWAI UNIT PELAYANAN PADA DINAS PERINDUSTRIAN DAN TENAGA KERJA KABUPATEN PURWOREJO (Jurnal Riset Mahasiswa, 2024)
This study aims to 1) Understand the performance of the employees of the service unit at the Department of Industry and Manpower of Purworejo Regency. 2) Understanding the causes of the employee performance of the Purworejo Regency Industry and Manpower Service unit are not optimal. 3) Understand the efforts to improve the performance of the employees of the Service Unit of the Industry and Manpower Office of Purworejo Regency. This research uses descriptive qualitative research. The results showed that: 1) Employee performance at the Department of Industry and Manpower of Purworejo Regency showed sufficient results. 2) The performance of the employees of the Office of Industry and Manpower of Purworejo Regency is not optimal due to the reduced motivation of employees at work, seen from frequently arriving late, postponing work, and utilizing office facilities for personal gain as well as complaints from several visitors that the slow process of administering this shows decrease in the quality of performance of the employees of the Purworejo Regency Industry and Manpower Office, limited facilities and infrastructure and mastery of industrial technology. 3) Efforts to improve the performance of the employees of the Purworejo Regency Industry and Manpower Office are to apply the work discipline of the State Civil Apparatus, implement a target system in payroll, internal supervision, external supervision, create a situation and climate that is conducive to the State Civil Apparatus, providing incentives and providing compensation.
Keywords: Performance; ASN; Dinperinaker